Synthesis of the structure of information and analytical support decision making commander of the military unit of Interior Troops participating in the phase of the power of special operations to end riots - Rozanova, L. V.; Kovalev, I. V.; Muzychuk, V. A. (Honor and Law, 2019)
The sources and consumers of information are needed for information-analytical support of troops during operations to stop the riots. A synthesis of approaches to rational structure of information and analytical support decision making commander of the military unit of Interior Troops to participate in the power stage special operation to stop the riots.